2009
DOI: 10.1021/es802042d
|View full text |Cite
|
Sign up to set email alerts
|

Degradation and Elimination of Various Sulfonamides during Anaerobic Fermentation: A Promising Step on the Way to Sustainable Pharmacy?

Abstract: Antibiotics, most notably sulfonamides and tetracyclines, are frequently used veterinary pharmaceuticals in animal husbandry. A new field of application for animal manure is in biogas plants for generating environmentally friendly energy. As a result, antibiotics contained in manure may still reach the environment as fermentation residues are also used on agricultural fields as fertilizers. Therefore, in fermentation tests seven sulfonamides and trimethoprim were investigated regarding their elimination behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(75 citation statements)
references
References 42 publications
6
63
0
5
Order By: Relevance
“…There were no sulfonamides and ionophores detected in the substrate and plant samples, suggesting degradation (and transformation) played a more important role in the aqueous removal of these two classes of antibiotics than substrate adsorption and plant uptake. The results are in good agreement with the previous reports that sulfonamides (including TMP used as sulfonamides potentiator) and MON are easily biodegradable (Xu et al, 2007;Mohring et al, 2009;Li and Zhang, 2010;García-Galán et al, 2011;Sun et al, 2014). For the detected 3 macrolides, adsorption onto substrates and uptake by plants only accounted for a minor percentage of the total mass loading into each CW.…”
Section: Removal Mechanism For Antibiotics and Argssupporting
confidence: 91%
“…There were no sulfonamides and ionophores detected in the substrate and plant samples, suggesting degradation (and transformation) played a more important role in the aqueous removal of these two classes of antibiotics than substrate adsorption and plant uptake. The results are in good agreement with the previous reports that sulfonamides (including TMP used as sulfonamides potentiator) and MON are easily biodegradable (Xu et al, 2007;Mohring et al, 2009;Li and Zhang, 2010;García-Galán et al, 2011;Sun et al, 2014). For the detected 3 macrolides, adsorption onto substrates and uptake by plants only accounted for a minor percentage of the total mass loading into each CW.…”
Section: Removal Mechanism For Antibiotics and Argssupporting
confidence: 91%
“…Higher removals have been reported for trimethoprim during nitrification process (Batt et al, 2006b;Perez et al, 2005) and anaerobic fermentation and sludge digestion (Gobel et al, 2005;Mohring et al, 2009), but it showed high persistence towards aerobic biological treatment (b20%) (Suarez et al, 2010). High aqueous removal percentage of trimethoprim in anoxic unite (39.5% and 53.2%) in plant A and in oxidation ditch (14.3% and 66.9%) in plant B further suggests that the removal of trimethoprim was attributed to the anoxic and anaerobic biodegradation process.…”
Section: Removal Mechanismsmentioning
confidence: 87%
“…These results indicated that sulfonamides were mainly biodegraded in the WWTPs. Sulfonamides (such as sulfamethoxazole, sulfamethazine, and sulfadiazine) have been reported to be easily biodegradable (Jesus Garcia-Galan et al, 2011;Li and Zhang, 2010;Mohring et al, 2009;Xu et al, 2011), and transformed in anaerobic sludge digestion (Gobel et al, 2005), while Suarez et al (2010) reported that sulfamethoxazole was minimally biodegradable (b 20%) under aerobic biological treatment. Previous papers also reported that for sulfonamides were little adsorbed onto the sludge, with sludge solid K d,solid ranging from 28.6 to 110 L/kg (Table S1).…”
Section: Removal Mechanismsmentioning
confidence: 99%
“…The results have demonstrated that anaerobic digestion (fermentation) is a very successful method to degrade SMX in sludge and manure with measured removal rates of >99 % after 10 to 35 days in batch-/lab-scale experiments. This impressive SMX degradation was achieved with both low (4 to 400 μg/L) (Carballa et al 2007) and high (2 to 10 mg/L) (Mohring et al 2009) initial SMX concentrations. In addition to these sludge and manure fermentation studies, anaerobic and anoxic column tests (as described in the previous section) were carried out with surface water containing 0.25 and 4.5 μg/L SMX in order to model microbial degradation during bank filtration.…”
Section: Anaerobic Degradationmentioning
confidence: 94%